BOK displays cell death‐independent tumor suppressor activity in non‐small‐cell lung carcinoma. Issue 10 (7th August 2017) - Moravcikova, Erika; Krepela, Evzen; Donnenberg, Vera S.; Donnenberg, Albert D.; Benkova, Kamila; Rabachini, Tatiana; Fernandez‐Marrero, Yuniel; Bachmann, Daniel; Kaufmann, Thomas
Abstract : As the genomic region containing the Bcl‐2‐related ovarian killer (BOK) locus is frequently deleted in certain human cancers, BOK is hypothesized to have a tumor suppressor function. In the present study, we analyzed primary non‐small‐cell lung carcinoma (NSCLC) tumors and matched lung tissues from 102 surgically treated patients. We show that BOK protein levels are significantly downregulated in NSCLC tumors as compared to lung tissues ( p < 0.001). In particular, we found BOK downregulation in NSCLC tumors of grades two ( p = 0.004, n = 35) and three ( p = 0.031, n = 39) as well as in tumors with metastases to hilar (pN1) ( p = 0.047, n = 31) and mediastinal/subcarinal lymph nodes (pN2) ( p = 0.021, n = 18) as opposed to grade one tumors ( p = 0.688, n = 7) and tumors without lymph node metastases ( p = 0.112, n = 51). Importantly, in lymph node‐positive patients, BOK expression greater than the median value was associated with longer survival ( p = 0.002, Mantel test). Using in vitro approaches, we provide evidence that BOK overexpression is inefficient in inducing apoptosis but that it inhibits TGFβ‐induced migration and epithelial‐to‐mesenchymal transition (EMT) in lung adenocarcinoma‐derived A549 cells. We have identified epigenetic mechanisms, in particular BOK promoter methylation, as an important means to silence BOK expression in NSCLC cells. Taken together, our data point toward a novel mechanism by which BOK acts as a tumor suppressor in NSCLC by inhibiting EMT. Consequently, the restoration of BOK levels in low‐BOK‐expressing tumors might favor the overall survival of NSCLC patients. Abstract : What's new? Bcl‐2‐related ovarian killer (BOK) is one of the most frequently deleted Bcl‐2 family members in human cancer. Here the authors identify a possible cell death‐independent tumor suppressor function of BOK. They find that BOK is epigenetically silenced and that its overexpression decreases anchorage‐independent growth in non‐small‐cell lung carcinoma (NSCLC). In vivo, BOK levels were predictive of survival in lymph node‐positive patients, pointing to BOK expression as a new prognostic marker in later stage NSCLC.